PEMBELAJARAN BERBASIS KECERDASAN MAJEMUK DALAM PENDIDIKAN ANAK USIA DINI - Fazrina, Farah; Fathoni, Isna Muhammad; Maspupah, Maspupah; Jaya, Ilham (Jurnal Anak Bangsa, 2024)
Intelligence cannot be measured only based on academic intelligence or IQ tests, but by looking at a person's ability to solve every problem (problem solving) and the ability to create new products that have cultural value (creativity). The aim of this research is to provide knowledge of multiple intelligence-based learning in early childhood education, and the application of multiple intelligence-based learning for early childhood. With this intelligence, students can adapt and learn from experience. According to Gardner, this learning model is a learning model that uses and applies multiple intelligence theory which needs to be prepared and designed well before the learning process is carried out. This research uses a descriptive qualitative method. The results of this research show that learning based on multiple intelligences in PAUD requires educators to have good creativity by using a variety of methods and shows that the application of learning based on multiple intelligences in PAUD can increase the activity and creativity of educators and students